Diagnostic delay and reducing the diagnostic interval in children with brain tumor - Shaban Mohamed, Mossad Abdelhak; Abdelhalim, Abdelbaset Taher (Universiti Islam Antarabangsa Sultan Abdul Halim Mu'adzam Shah (UniSHAMS), 2018)
Brain tumor account for a quarter of all childhood cancers, affecting about 1 in 2400 United Kingdom (UK) children under the age of 16 annually, while brain and other nervous system cancer incidence per 100,000 population in Peninsular Malaysia for age 0-19 years was 84/100000. Death occurs either as a result of catastrophic presentations with raised intracranial pressure or as a result of tumor recurrence and resistance to further treatment. Five-year survival rates became over 70%, and the majority of these patients go on to be long-term survivors. Despite this, 60% of long-term survivors of childhood brain tumors are moderately or severely neurologically disabled. Delayed diagnosis of brain tumor among children is a concern around the globe and has been reported by parents, in the media, and in the courts. These reports can disturb public confidence in healthcare systems. This literature searches studied diagnostic delay and reducing the diagnostic interval in children with brain tumor, using online databases and a manual search. Main keywords used were diagnostic delay, brain tumor in children and post symptomatic diagnostic interval. In some studies post symptomatic diagnostic interval (PDI) was 28 weeks with a parental delay of 11.1 weeks and a doctor's delay of 16.9 weeks. We concluded many recommendations as programmes to raise public and professional awareness of the symptomatology of brain tumor, early referral, CT scan fast track. Along with many other recommendations were discussed in this article.